The growth of military development in Southeast Asia: An arms race phenomenon or a normal development? - Keling, Mohamad Faisol; Shuib, Md. Shukri; Ajis, Mohd Na'eim
The Soviet Union’s collapse in 1991 had influenced Southeast Asian countries (SAC) to strengthen the defense system in ensuring the safety and sovereignty of the country.The change in international system has propelled SAC to develop and modernize their defense systems.This military modernization and development process has increased the quantity and quality of a country’s defense system.Hence, since the 1990s SAC have started to increase their import and ownership of modern weaponry in line with the current technology development.The increase in import of armaments and ownership of modern weaponry has however raised questions on military development in South-East Asia whether it has shaped an arms race or whether it is just a normal development, which is a country’s need especially in Southeast Asia region.